Play-Based Stimulation to Improve Coordination and Visual Movement Response of Elementary School Students - Naheria; Gyta Krisdiana Cahyaningrum; Nurjamal; Didik Cahyono; Muhammad Sukron Fauzi (MultiTech Publisher, 2024)
This study aims to identify the improvement of motor coordination and visual movement response in elementary school students through physical activity-based game stimulation. The research was conducted using a quasi-experimental method, with pre-test and post-test to measure the development of students' abilities. This study uses a quasi-experimental design with a pre-test and post-test approach to measure changes in students' motor coordination and visual movement responses. The sample used was elementary school students with a total of 40 people. The results of the study showed a significant improvement in students' motor coordination ability, where 45% of students in the pre-test were in the category of excellent coordination, and increased to 85% in the post-test, showing an increase of 40%. In addition, students' visual motion response also improved significantly, with a decrease in reaction time from 300 ms in the pre-test to 150 ms in the post-test, indicating an improvement in the ability to respond to visual stimuli. Games such as throwing and touching the cone have been proven to be effective in stimulating improved motor coordination and visual response of students. This study concludes that stimulation through play has a positive impact on improving students' motor and cognitive abilities